Blue–Red LED Light Modulates Morphophysiological and Metabolic Responses in the Medicinal Plant Nepeta nuda - Miroslava Zhiponova; Grigor Zehirov; Krasimir Rusanov; Mila Rusanova; Miroslava Stefanova; Tsveta Ganeva; Momchil Paunov; Valentina Ganeva; Kiril Mishev; Petre I. Dobrev; Roberta Vaculíková; Václav Motyka; et al. (Plants)
Light quality and duration profoundly influence the growth and productivity of plant species. This study investigated the effects of a blue–red LED light combination, known to induce flowering, on the physiological state and content of biologically active substances in catmint (Nepeta nuda L.) grown under controlled in vitro conditions. White light (W) was used as a control and compared with two blue–red intensities: BR (high-intensity blue–red light) and BRS (low-intensity blue–red light or “BR with shadow”). BR-treated plants showed increased leaf area, mesophyll thickness, biomass and starch content but reduced levels of plastid pigments. BR also modified the oxidative state of plants by inducing lipid peroxidation while simultaneously activating ROS scavenging mechanisms and enhancing phenolic antioxidants. Interestingly, BR decreased the accumulation of the Nepeta sp.-specific iridoid, nepetalactone. These effects appear to be regulated by the phytohormones auxin, abscisic acid and jasmonates. BRS treatment produced effects similar to the W control but led to increased plant height and reduced leaf area and thickness. Both BR and BRS regimes induced the accumulation of proteins and amino acids. We conclude that blue–red light can enhance the survival capacity of micropropagated N. nuda during subsequent soil adaptation, suggesting that similar light pre-treatment could improve plant performance under stress conditions.